The Challenge of Flood Devastation in India Every Year : The Likely Solutions - Prasad, Mahesh (AMC Indian Journal of Civil Engineering, 2020)
The flood problem in India is a chronic issue, the rivers causing devastation almost every year in certain regions of the states like Bihar, Uttar Pradesh, Assam, Kerala, Karnataka, Madhya Pradesh, Gujarat, Odisha, and Bengal. This is happening despite the huge investments done so far in various river valley projects since Independence. Merely attributing the problem to issues like climate change, deforestation issue, and rapid growth in habitations is not enough and certain out of the box thinking is needed to resolve the issue. The article brings out certain untraditional measures, short term as well as long term, which if implemented may reduce and check this chronic problem which is causing large scale physical and mental distress to affected population apart from causing huge losses to nation in the form of damage to crops and other assets.